Aggressive Medicine Promotional Activity of Pharmaceutical Industry All Over the Globe: Who Will Do the Highly Risky Job to Defy the Monstrous Financial Tyrant? (Bangladesh Journal of Medical Science, 2020)
Abstract Not AvailableBangladesh Journal of Medical Science Vol.19(4) 2020 p.589-593